Well-posedness of boundary value problems for reverse parabolic equation with integral condition - Charyyar Ashyralyyev (E-Journal of Analysis and Applied Mathematics)
Reverse parabolic equation with integral condition is considered. Well-posedness of reverse parabolic problem in the Hölder space is proved. Coercive stability estimates for solution of three boundary value problems (BVPs) to reverse parabolic equation with integral condition are established.